THE PHYSICS TEACHER’S TRAINING TO PLANNING INFORMATIVELY EDUCATIONAL ENVIRONMENTS - Borovik, O.M. (Journal of Information Technologies in Education (ITE), 2010)
It is examined questions, related to the studies of physics teachers to planning of educational environments in postgraduate education system, in the article